Association of hyperlipidaemia in preterm delivery - Kundoor, Ruthvika; Sandhya Rani, Burri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Premature infant is the most important outcome of preterm delivery and is also the cause for infant mortality after congenital abnormality. Around the world, there are 3.6 million per year neonatal deaths, of which in developing countries, 99% deaths are observed. This study was conducted to evaluate the elevated triglycerides and cholesterol relationship on preterm labor risk. Methods: 350 healthy pregnant women were included in the study group in the age group of 18-36 years, their gestational age was confirmed either by last menstrual period or by ultrasound. This study was conducted in Department of Obstetrics and Gynaecology at Osmania University, Hyderabad, Telangana India. Results: The good outcomes were observed in mothers with normal cholesterol values and preterm deliveries were observed in 32.14% of mothers with abnormal cholesterol values. 0.3% of mothers with normal triglyceride values and 75% of mothers with abnormal values had preterm delivery. P value difference was statistically significant (P<0.05). Conclusions: By measuring serum total cholesterol and triglycerides, along with serum screening of α-fetoprotein and inhibin A, it can be used to predict the preterm labour.